مشاركة المجلس الشعبي البلدي في إعداد المخططات العمرانية في القانون الجزائري - قادري, طارق (جامعة الوادي University of Eloued, 2019)
ملخص: يشارك المجلس الشعبي البلدي في إعداد المخطط التوجيهي للتهيئة والتعمير ومخطط شغل الأراضي الى جانب رئيس المجلس الشعبي البلدي، من خلال إقرار إعداد المخططين بموجب مداولة من المجلس الشعبي البلدي المعني أو المجالس الشعبية البلدية المعنية، ويظهر دوره أيضا بإخضاع جميع مقررات المؤسسة العمومية المشتركة بين البلديات التي تتخذها في إطار إعداد المخططين لمداولة المجلس الشعبي البلدي المعني أو المجالس الشعبية البلدية المعنية أيضا، وأخيرا التداول في مرحلة لاحقة بخصوص المصادقة على المخططين. الكلمات المفتاحية: مشاركة؛ المجلس؛ الشعبي؛ البلدي؛ إعداد؛ المخططات؛ العمرانية؛ القانون؛ الجزائري. Abstract: The Municipal Popular Assembly participates in the preparation of the outline for the preparation and reconstruction and the plan of filling the land along with the Chairman of the assembly, through the approval of the preparation of the planners under a deliberation from assembly concerned; it's role can be seen in the subordination of all the decisions of the common public institution between the municipalities taken as a part of the framework of preparing the planners for the deliberation of the municipal Assembly or also the concerned municipal councils, and finally deliberating at a later stage regarding the approval of the planners.
L Participation Of The Municipal Popular Assembly In The Preparation Of Urban Plans In Algerian Law
Keywords: مشاركة؛ المجلس؛ الشعبي؛ البلدي؛ إعداد؛ المخططات؛ العمرانية؛ القانون؛ الجزائري.; contribution - assembly - people - Municipal - Preparation - Plans - Urban - Law - Algerian